Diffusion-Weighted Imaging of Hyperacute Cerebral Hypoglycemia - Schmidt, P. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Cerebral hypoglycemia can result in reversible metabolic brain insults and can be associated with impaired diffusion disturbances. Our aim was to evaluate possible changes in DWI of the human brain during hyperacute short-term severe hypoglycemia. MATERIALS AND METHODS: Ten individuals scheduled for a clinical IST were examined with DWI while the test was performed. Venous blood glucose was continuously measured, and sequential DWI sequences were performed without interruption. Hypoglycemia was terminated with intravenous glucose administration when glucose levels were at ≤2.0 mmol/L. RESULTS: Blood glucose levels were lowered to a mean nadir of 1.75 ± 0.38 mmol/L. No alterations of cerebral diffusion could be observed in any individuals on DWI. CONCLUSIONS: Hyperacute short-term severe hypoglycemia does not induce visible changes in DWI of the human brain.